Exploring ‘Human’: A Comparative Linguocultural Inquiry across English, Russian, and Uzbek - Ismatullayeva Marjona (Indonesian Journal Publisher, 2025)
Through this investigation, the researchers examine the definition of human in English, Russian, and Uzbek using comparative linguocultural methodology. The fundamental human concept undergoes perceptual modification because of linguistic influence despite its inadequate study across multiple languages. Previous research has studied the concept of humans within individual languages, but there is insufficient systemic analysis between various linguistic traditions. The current investigation utilizes dictionary definitions and corpus-based and discourse analysis to conduct an intercultural examination of humans in English, Russian, along Uzbek. Each language demonstrates universal and specific linguistic features manifest in individualistic agency, followed by collectivist moral responsibility and communal social regulations. Historical, philosophical societal factors thus determine how language expresses humanity. These research findings help advance cognitive linguistics in addition to intercultural communication and translation studies due to evidence showing why translations from direct words lack full cultural contextual meaning. Evaluating these conceptual distinctions helps us understand people from different cultures and improves both communication between them and their mutual understanding. This study shows why combining cultural viewpoints matters for linguistic sciences while providing real-world benefits to translators and diplomats. Future investigations should include more research languages and experimental approaches to enhance our knowledge about language's function as an identity encoder.